ENSURING EFFECTIVE USE OF ICT IN TEACHING AND LEARNING - Fengchun, Miao; Nanaieva, Tatiana (Електронне наукове фахове видання “ВІДКРИТЕ ОСВІТНЄ Е-СЕРЕДОВИЩЕ СУЧАСНОГО УНІВЕРСИТЕТУ”, 2016)
The article delineates UNESCO’s vision about the role, challenges and opportunities of ICT in modern education. It analyzes the impact of ICT on equal access to quality education, possibilities of open educational resources and systems, the need to rethink approaches to assessment of the quality of education and the role of teachers, challenges and opportunities of distance education, etc. The article determines that the main factors which make possible the effective implementatio n of ICT in education are the result-oriented information and communication technologies in education policy, pupil-centered and student-centered ICT learning environment and individualized couching pedagogy. It is pointed to the need for creating government policy for transformation of education with ICT and its implementation at all levels of education.